2017
DOI: 10.3844/ojbsci.2017.136.142
|View full text |Cite
|
Sign up to set email alerts
|

Response of Different <i>Agrobacterium Rhizogenes</i> Strains for <i>in vitro</i> Hairy Root Induction and Accumulation of Rosmarinic Acid Production in <i>Agastache Rugosa</i>

Abstract: In this study a total of seven different Agrobacterium rhizogenes strains were evaluated for their ability to transform the plant Agastache rugosa and to produce the secondary metabolite rosmarinic acid. All the strains of A. rhizogenes i.e., 13333, 15834, A 4, LBA9402, R1000, R1200 and R1601 strains tested here in this study, were able to induce hairy root formation in leaf tissue explants. The strain A 4 had the highest rate of infection (94.1±8.3%) and the strain R1000 had the lowest rate (88.6±6.9%). The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Several previous studies have stated that the A4 strain can be used to induce HR in medicinal plants, such as Aesculus hippocastanum ( Zdravković-Korać et al., 2004 ), Boerhaavia diffusa ( Gupta et al., 2016 ), Catharanthus roseus ( Batra et al., 2004 ), Gentiana macrophylla ( Tiwari et al., 2007 ), Hypericum perforatum ( Vinterhalter et al., 2006 ), O. basilicum ( Srivastava et al., 2016a ; Abadi et al., 2020 ; Pandey et al., 2022 ), Rhaponticum carthamoides ( Skała et al., 2015 ), and Scutellaria baicalensis ( Tiwari et al., 2008 ). Among the different strains tested for HR induction and SM production in the plants such as A. rugosa , F. tataricum , M. alba , the most effective strains were A. rhizogenes ATCC 13333, R1000, and LBA9402, respectively ( Thwe et al., 2016 ; Park et al., 2017a ; Park et al., 2017b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies have stated that the A4 strain can be used to induce HR in medicinal plants, such as Aesculus hippocastanum ( Zdravković-Korać et al., 2004 ), Boerhaavia diffusa ( Gupta et al., 2016 ), Catharanthus roseus ( Batra et al., 2004 ), Gentiana macrophylla ( Tiwari et al., 2007 ), Hypericum perforatum ( Vinterhalter et al., 2006 ), O. basilicum ( Srivastava et al., 2016a ; Abadi et al., 2020 ; Pandey et al., 2022 ), Rhaponticum carthamoides ( Skała et al., 2015 ), and Scutellaria baicalensis ( Tiwari et al., 2008 ). Among the different strains tested for HR induction and SM production in the plants such as A. rugosa , F. tataricum , M. alba , the most effective strains were A. rhizogenes ATCC 13333, R1000, and LBA9402, respectively ( Thwe et al., 2016 ; Park et al., 2017a ; Park et al., 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…This supports the results of our study, which showed that the lowest rosmarinic acid content was obtained in the ATCC 15834 infected strain. In another study, A. rugosa transformed with different Agrobacterium strains showed that ATCC 13333 strain is suitable for increasing rosmarinic acid production ( Park et al., 2017b ). In F. tataricum , the highest total phenolic content was observed in the R1000 strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation